Strangers in the Land of their Birth: Concepts of Social Integration in Portrayals of the Malay in Contemporary Malaysian Novels in English - Eng, Chuah Guat (SARE: Southeast Asian Review of English, 2017)
This paper interrogates the positioning of MLE writers as strangers in the land of their birth by taking a sociology-based (as opposed to an ideology-based or ethnocentric) approach to the study of how Malays and the Malay world are portrayed in MLE novels. This approach is part of a larger research project aimed at developing a new, sociology-based paradigm for MLE studies.